Retrospective Review of Nasofaring Carcinoma in Wahidin Sudirohusodo General Hospital on 2011-2019 Period - Andi Bachri; Nani Iriani Djufri (TALENTA PUBLISHER, 2020)
Introduction: Nasopharyngeal carcinoma is the most common head and neck malignant tumor in Indonesia (60%), followed by malignant nasal and paranasal sinuses (18%), and larynx (16%). Prevention of Nasopharyngeal Carcinoma is still a problem; this is because the etiology is still uncertain; early symptoms are not typical. Objective: The primary objective of this study was to review nasopharyngeal carcinoma cases based on gender, stage, ethnicity, and complaints in Wahidin Sudirohusodo hospital. Methods: This was a retrospective study to review the case of nasopharyngeal carcinoma in Wahidin Sudirohusodo hospital from January 2011 to June 2019 with total samples of 280 cases. Samples were taken from medical records, and the data about gender, ethnicity, stage of the tumor, and complaints were collected. Results: Complaints felt by patients were generally due to a neck lump in 175 cases (62.5%), Blood staine rinore 45 cases (16%), tinnitus 25 cases (8.9%), cephalgia 5 cases (1 7%). Comparison of patients with nasopharyngeal carcinoma according to sex, men compared with women 2:1, namely men 188 cases (67.14%) and women 92 cases (32.86%). The origin of the nasopharyngeal carcinoma patients was the Bugis-Makassar tribe 178 cases (63.57%), the Toraja tribe as many as 32 cases (11.43%), Java 10 cases (3.57%), Mandar 4 cases (1.43%), others 56 cases (20%). The stages of the nasopharyngeal carcinoma were stage IV 160 cases (57.14%), stage III 57 cases (20.36%), stage II 49 cases (17.5%), stage I 14 cases (5%). Conclusion: 280 cases of nasopharyngeal carcinoma have been treated with a male ratio of 188 people: 92 women or 2: 1, this is the same as previous studies. The youngest age is found at 9 years as many as 3 people. The youngest age ever reported in Semarang is 4 years. Furthermore, most cases come in stage IV.